GROWING DEVELOPING CIVICS LITERACY THROUGH SAINTIFIC LEARNING APPROACH MODEL USING LEARNING MEDIA COMPUTER PRO SHOW GOLD APPLICATION - Fatahillah Fatahillah; Mulat Sudrajat; Ari Rohmawati (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2018)
Developing Civic Literacy for a citizen of a young country is a pedagogical mission that must be borne by every educator directed by the 2013 Curriculum through the use of Scientific approaches in various learning activities that require learning media that can arouse students' rational and intellectual thinking ability, namely Audio Visual Media namely a media based on multimedia with computer hardware and run based on software programs namely; Pro Gold Show. Researchers intend to carry out an Action Research (Action Research) which aims to examine the Impact of the Use of Scientific Learning-Based Models Using Computer Application Media Pro Gold Show Research will be carried out through three cycles namely planning, acting, observing and Reflection and analyzed by SWOT (Strenghts Weakness Opportunities Threats). This study was conducted to develop a hypothetical model using a qualitative approach, while the results of the study showed that the Action Model had the power: Can provide a more effective and simple transformation of knowledge through a series of stages of Action, Weaknesses: Learning using an old style that is Cross Curricular will hinder innovation and improvisation: Opportunities: Still open Innovation and Improvisation in its development; Threat: Creativity that is not formed due to the lack of ability of the Teacher will result in actions in learning to be in vain.